IRIGASI TERKENDALI CERDAS MENGGUNAKAN INTERNET OF THINGS DAN TANTANGAN DALAM MENINGKATKAN EFISIENSI PENGGUNAAN AIR - Nurandani Hardyanti; Badrus Zaman; Widi Widayat; Aen Hendrawati; Sandra Anggita Sari; Budihardjo, Mochamad Arief (Fakultas Teknik Universitas Wahid Hasyim, 2025)
In order to execute sustainable agriculture, an agricultural system is required, particularly an effective and efficient irrigation system, to maximize the use of available water while minimizing water waste. For these reasons, a technological approach is required to implement more efficient irrigation and be environmentally friendly. Smart irrigation systems utilizing data-driven techniques such as the Internet of Things (IoT) that minimize the environmental footprint are one of the current technological approaches on the rise. However, studies on this topic's challenges and prospects have been conducted and still need to be completed. This study aims to provide a more thorough understanding of the use of smart irrigation so that it can be more widely adopted. Recent studies on sophisticated irrigation management principles and smart irrigation monitoring are highlighted. Researchers will be able to use this review to identify directions and gaps for upcoming research activities in this area and monitor and develop control prospects associated with irrigation agriculture. Keyword: Water Use Efficiency, Internet of Things (IoT), Smart Irrigation, Sustainable Agriculture, Irrigation Monitoring and Control